NextGenerationEU in major Italian cities - Gargiulo, Carmela; Guida, Nicola; Sgambati, Sabrina (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The European Union has reacted to the pandemic with the program NextGenerationEU (NGEU) to boost the recovery and development of the EU countries by relying on National Recovery and Resilience Plans (NRRPs). Given the pivotal role of cities, and in particular major cities, as engines of social and economic growth, the success of the program necessarily depends on the increase of urban competitiveness, intended as an intrinsic characteristic of cities and a fundamental aspect to transforming resources and challenges into opportunities for territorial development. This paper examines the relationships between major cities and the NRRP in the Italian context, firstly highlighting the role of cities in the plan’s different phases and then drawing attention to the missions and investments in which the urban dimension is more significant. Furthermore, it highlights how the NRRP goals achievement in cities can lead to higher levels of competitiveness and support the national economic recovery. One of the main results is the identification of five Macro-areas of Competitiveness for the urban dimension: Tourism and culture, Digitalization/smartness, Green transition, Sustainable mobility, Social Inclusion & Cohesion. Additionally, the paper discusses the allocation of the European resources among major Italian cities in relation to their urban suitability and vocations.